2003
DOI: 10.1038/sj.ijo.0802440
|View full text |Cite
|
Sign up to set email alerts
|

Energy cost of physical activities in 12-y-old girls: MET values and the influence of body weight

Abstract: BACKGROUND: Few data exist on the energy cost of specific activities in children. The influence of body weight on the energy cost of activity when expressed as metabolic equivalents (METs) has not been vigorously explored. OBJECTIVE: To provide MET data on five specific activities in 12-y-old girls and to test the hypothesis that measured MET values are independent of body weight. SUBJECTS AND METHODS:In 17 12-y-old girls, resting metabolic rate (RMR) and the energy expended while sitting, standing, walking on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 17 publications
2
39
0
1
Order By: Relevance
“…However, the present review has shown that it is much less good at assessing physical activity behaviour especially within most current population groups which include a majority of Energy balance and obesityoverweight and obese individuals. For these groups the lack of any change in the distribution of PAL values or absolute rates of PAEE is almost certainly concealing marked behavioural changes in activities which are revealed by different methodologies such as accelerometry (68,69) , and are, in fact, easily identifiable if weightcorrected values of PAEE are used instead of PAL. The further development of such methodologies and their application in future DLW studies would markedly improve understanding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the present review has shown that it is much less good at assessing physical activity behaviour especially within most current population groups which include a majority of Energy balance and obesityoverweight and obese individuals. For these groups the lack of any change in the distribution of PAL values or absolute rates of PAEE is almost certainly concealing marked behavioural changes in activities which are revealed by different methodologies such as accelerometry (68,69) , and are, in fact, easily identifiable if weightcorrected values of PAEE are used instead of PAL. The further development of such methodologies and their application in future DLW studies would markedly improve understanding.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, it has been argued that it may not be possible to adjust PAEE for size with any confidence and that great caution must be exercised when attempting to do so (67) . In 12-year-old girls the energy cost of walking at fixed speeds increased with body weight, especially at higher walking speeds (68) . In these latter studies MET values (EE/RMR) for walking at a 10 % incline at 4·8 mph for girls of 50 kg was about 40 % higher than girls of 30 kg, an increase which is obviously less than the 66·6 % difference that would have occurred if the MET values were simply corrected by weight.…”
Section: Direct Measurements Of Energy Expenditurementioning
confidence: 99%
“…Children data were collected and published by various authors (e.g. Bandini et al 2006, Spadano et al 2003, 2005, Torun, 1989 and are used to calculate daily energy and nutritional requirements. Again, no school related data were available so far and these are provided in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The values observed in this experiment for theory lessons are higher than the RMR for the age group (Black et al 1996). Spadano et al (2003) The values for the present youngest group, which is a year older and has a higher weight than…”
Section: Metabolic Ratementioning
confidence: 99%
“…The assumption underlying the use of PAL is that by adjusting for RMR and expressing the data as a ratio the potential influence of body weight and composition is removed, thus allowing comparisons of the relative energy cost of physical activities between individuals and populations. Although this assumption may be valid for sedentary or low-intensity activities, PAL is not necessarily independent of body weight or FFM (Spadano et al 2003(Spadano et al , 2005, particularly in weight-bearing activities of moderate-vigorous intensity, such as walking Fig. 1.…”
Section: Physical Activity Energy Expenditure and Body Fatnessmentioning
confidence: 99%